Associative learning and recollection of olfactory memory during the respiratory cycle in mammals: how is the self cognized in consciousness? - Mori, Kensaku; Sakano, Hitoshi (Frontiers in Neuroscience, 2025)
When we are awake and relaxed, various memory-scenes come up in our mind by spontaneous activation of memory engrams. We find ourselves in the memory-scene longing for it by the present self. The memory scene is also recollected by sensory inputs from the surrounding world for learned behavioral decisions. It is well experienced that odorants act as strong cues in remembering associated memory. Associative learning of odor signals and object cognition enables us to predict cognitive imagery of an environmental object. Here, we discuss the neural network connecting the olfactory cortices to the higher cognitive areas that dynamically switches the processing mode from feedforward to top-down. These processes are correlated with the respiratory cycle to form and recollect odor-object associative memory. We infer that during the inhalation phase, feedforward odor signals drive burst firings of a specific subset of pyramidal cells in the olfactory cortex. In contrast, during the subsequent late-exhalation phase, top-down cognitive scene-signals from the higher areas activate again the same pyramidal cells as those activated by the feedforward signals. Reactivation of pyramidal cells during the exhalation phase may induce plastic changes in the inter-areal synaptic connections in the neural network to form associative-learning memory. In this perspective article, we will discuss associative learning and cognition of self in the mammalian olfactory system.